2009
DOI: 10.1182/blood-2009-02-203307
|View full text |Cite
|
Sign up to set email alerts
|

Impact of donor CMV status on viral infection and reconstitution of multifunction CMV-specific T cells in CMV-positive transplant recipients

Abstract: Reconstitution of cytomegalovirus (CMV)-specific CD8 ؉ T cells is essential to the control of CMV infection in CMV-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
111
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 63 publications
18
111
2
3
Order By: Relevance
“…Nevertheless, the mere presence of these functional T-cell types was associated with lower levels of CMV replication within episodes of active CMV infection, and hence with a shorter duration of episodes. This is in line with previously published data (Lilleri et al, 2008;Muñoz-Cobo et al, 2012;Zhou et al, 2009), and further highlights the crucial role of adaptive T-cell immunity in the control of CMV viraemia in Allo-SCT recipients.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, the mere presence of these functional T-cell types was associated with lower levels of CMV replication within episodes of active CMV infection, and hence with a shorter duration of episodes. This is in line with previously published data (Lilleri et al, 2008;Muñoz-Cobo et al, 2012;Zhou et al, 2009), and further highlights the crucial role of adaptive T-cell immunity in the control of CMV viraemia in Allo-SCT recipients.…”
Section: Discussionsupporting
confidence: 81%
“…4 Furthermore, 60% of the cohort underwent myeloablative conditioning. Interestingly, our assertion that strategies that result in full donor chimerism might offer little antiviral protection in the context of R1/D2 transplants is supported by the clinical outcome data of these studies, 4,5 as well as by a smaller study that demonstrated persistence of recipient-derived CMV-specific T cells in T-deplete but not T-replete HSCT. 12 The latter study used an in vitro T-cell depletion strategy with Campath-1M plus complement, which results in depletion of mainly donor T cells while leaving recipient T cells intact.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In high-risk cases in which the recipient is seropositive, this is likely to be the most prolonged when the donor is seronegative (D2), as immunity is then reliant on the development of a primary immune response. [3][4][5] After myeloablative conditioning, the establishment of protective immunity may be delayed still further by the incorporation of T-cell depletion strategies aimed at reducing the risk for graft-vs-host disease (GvHD).…”
Section: Introductionmentioning
confidence: 99%
“…Also, impaired function of regulatory T cells (e.g., through conditioning regimens or immunosuppression) could play a role (34). However, also transplantation of quiescent autoreactive T cells in the grafts could lead to subsequent activation and amplification of such cells in the absence of an effective immunosurveillance during transplantation (38,39). Because we did not detect any autoreactive T cells in donor samples, the first mechanism seems to be more likely.…”
Section: Discussionmentioning
confidence: 66%